From Forest to Village: Myths and Tiger Attacks in Kerinci During the Dutch East Indies (1903-1942) - Hudaya, Padhil; Widyonarko, Bambang (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2025)
The people of Kerinci have their own interpretation of the tiger. Tigers are considered sacred animals, with various meanings. However, on the other hand, tigers that attacked the people of Kerinci during the Dutch East Indies were still killed. This study aims to look at the relationship between the myths that developed and the attacks carried out by Sumatran tigers against people in Kerinci during the Dutch East Indies Government. With the approach of human and animal relations in the perspective of local traditions, this research analyzes the influence of local mythological narratives, the causes of tiger attacks on the community, and the steps taken to overcome these attacks. This research uses the historical method as a scalpel, with the flow of heuristics, source criticism, interpretation and historiography. Data were collected from various historical sources, such as colonial archives, ethnographic records, as well as local oral traditions about tigers. The research findings show that tiger myths associated with spiritual symbols play an important role in shaping people's perceptions of the species. However, attacks by tigers caused by disturbed areas of their habitat led to a reaction by placing tigers as a threat to security and interfering with the exploitation of natural resources.